Field notes contributed by Babs Padelford and Loren Padelford, spring 1992 - Padelford, Babset al; Padelford, Lorenet al (1992)
List of birds and locations contributed by Babs Padelford and Loren Padelford with observers Jerry Toll and B.J. Rose. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1992. Plustek - flatbed